2021
DOI: 10.1128/mbio.00229-21
|View full text |Cite
|
Sign up to set email alerts
|

The Novel P II -Interacting Protein PirA Controls Flux into the Cyanobacterial Ornithine-Ammonia Cycle

Abstract: Among prokaryotes, cyanobacteria have an exclusive position as they perform oxygenic photosynthesis. Cyanobacteria substantially differ from other bacteria in further aspects, e.g., they evolved a plethora of unique regulatory mechanisms to control primary metabolism. This is exemplified by the regulation of glutamine synthetase (GS) via small proteins termed inactivating factors (IFs). Here, we reveal another small protein, encoded by the ssr0692 gene in the model strain Synechocystis sp. PCC 6803, that regul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 92 publications
2
24
0
Order By: Relevance
“…In vitro, PirA binds to PII-ADP to tune down the PII-promoted activation of NAGK, the PII-controlled enzyme of arginine biosynthesis [6,8,[21][22][23]. In agreement with these findings, overproduction of PirA reduced arginine levels, whereas in the absence of PirA overproduction of arginine and related metabolites was observed [66]. Together, these data suggest that, in response to ammonium-upshift conditions, PirA antagonizes the PII-promoted activation of NAGK to re-equilibrate arginine levels (Figure 3).…”
Section: Open Accesssupporting
confidence: 67%
See 1 more Smart Citation
“…In vitro, PirA binds to PII-ADP to tune down the PII-promoted activation of NAGK, the PII-controlled enzyme of arginine biosynthesis [6,8,[21][22][23]. In agreement with these findings, overproduction of PirA reduced arginine levels, whereas in the absence of PirA overproduction of arginine and related metabolites was observed [66]. Together, these data suggest that, in response to ammonium-upshift conditions, PirA antagonizes the PII-promoted activation of NAGK to re-equilibrate arginine levels (Figure 3).…”
Section: Open Accesssupporting
confidence: 67%
“…The second small protein that interacts with PII, product of ssl0692 in Synechocystis, is 51 amino acids long and is named PirA [66]. PirA shows the inverse expression compared with PirC, being repressed by NtcA and accumulating following ammonium upshift.…”
Section: Open Accessmentioning
confidence: 99%
“…In particular, the role of small proteins as effectors for the activity of key enzymes receives more and more attention (for a review see [ 31 ]). One such small protein is PirA ( P II - i nteracting r egulator of a rginine synthesis) which has recently been shown to modulate arginine synthesis via competition with NAGK for P II binding [ 32 ]. As binding of NAGK to the P II protein reduces the effect of feedback inhibition, PirA interferes with arginine accumulation and acts as indirect inhibitor of NAGK.…”
Section: Introductionmentioning
confidence: 99%
“…As binding of NAGK to the P II protein reduces the effect of feedback inhibition, PirA interferes with arginine accumulation and acts as indirect inhibitor of NAGK. Similar to gifA and gifB , which encode the two known proteinaceous GS inhibitors IF7 and IF17, expression of the pirA gene (Gene ID: ssr0692 ) increases with rising N availability due to relief from NtcA-mediated transcriptional repression [ 24 , 32 ]. Moreover, novel RNA-based mechanisms regulating N assimilation have been described in Synechocystis and other cyanobacteria [ 33–35 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the downregulation of genes related to nitrogen assimilation is mediated via the nitrogen‐sensing protein P II (Schwarz et al ., 2014), which was found to be static at protein levels but with an altered phosphorylation state (discussed below). Interestingly, the P II interaction regulator of carbon storage metabolism, PirC, is highly abundant at HC conditions and is downregulated at LC conditions, whereas the P II interaction regulator of the arginine synthesis, PirA, shows opposite trends (Bolay et al ., 2021; Orthwein et al ., 2021). Furthermore, proteins involved in the biosynthesis of the molybdopterin cofactor that is part of the nitrate reductase (Lin & Stewart, 1998) are also found among the downregulated proteins in LC‐shifted cells.…”
Section: Resultsmentioning
confidence: 99%